PENGEMBANGAN MEDIA PEMBELAJARAN TEKA-TEKI SILANG (TTS) PADA PEMBELAJARAN TEMATIK TEMA CITA-CITAKU KELAS IV DI MI AL BUSYRO - Siti Nurjanah; Sumarmi (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2020)
The use of instructional media really helps teachers develop and deepen the teaching and learning process in the classroom. The use of instructional media that varies appropriately can affect student learning activities, interests and motivation. Therefore, learning media that are not boring are needed. One of them is with game-based media, such as crossword puzzles. Based on the background and study of the theory, this research is expected to provide answers to the formulation of the problem: (1) What is the validity of the crossword puzzle media on the thematic learning of my ideals for grade IV at MI Al-Busyro? (2) What is the practicality of the crossword media in the thematic learning theme of my ideals grade IV at MI Al Busyro? (3) What is the effectiveness of the crossword puzzle media on the thematic learning of my ideals for grade IV at MI Al Busyro ?. The objectives in this study are (1) Knowing the validity of the crossword puzzle media on the thematic learning theme of my ideals grade IV at MI Al Busyro? (2) Knowing the practicality of the crossword media in the thematic learning theme of my ideals grade IV at MI Al Busyro? (3) Knowing the effectiveness of the crossword puzzle media in the thematic learning theme of my ideals grade IV at MI Al Busyro ?. This research is a type of research or development known as Research and Development (R&D). This research was conducted in MI Al-Busyro class IV. The instrument used in the form of a validation sheet to measure validity, questionnaire responses of teachers and students to measure the level of practicality, and items to measure the level of effectiveness through student tests. The data that has been obtained is then analyzed using qualitative and quantitative descriptive data analysis. Based on the results of the validity analysis, (1) The crossword puzzle media developed are in the very valid category with a value of 90.5%. (2) The results of the teacher's response questionnaire were 93% and the results of the student's questionnaire responses were 90% and each was in the very good category. (3) The percentage of student graduation is more than 85%. Thus, it can be concluded that the developed crossword puzzle media meet valid, practical and effective categories.